PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP PRESTASI BELAJAR SISWA MATERI JARING-JARING BANGUN RUANG KELAS V SDN 04 PARAKANNYASAG - Reza Zulfa Fakhriyyah; Meiliana Nurfitriani; Anggia Suci Pratiwi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to investigate the effect of the Project Based Learning model on students' academic achievement in the topic of three-dimensional nets in Grade V at SDN 04 Parakannyasag.The research employed a quantitative approach with an experimental method, using a Nonequivalent Control Group Design. The population of the study consisted of all fifth-grade students at SDN 04 Parakannyasag, totaling 35 students.Based on the results of the study, the average pretest scores of the experimental and control classes were 41.17 and 30.59, respectively. The average posttest score in the experimental class was 84.17, while the control class scored 52.59. These results show that the posttest average score of the experimental class was higher than that of the control class.Furthermore, based on several statistical analyses conducted namely the normality test, homogeneity test, and hypothesis testing the hypothesis test at a significance level of 0.05 yielded a result of 0.000 < 0.05. This means that H₁ is accepted and H₀ is rejected, indicating that the Project Based Learning model has a significant effect on students’ academic achievement in the topic of three-dimensional nets in Grade V at SDN 04 Parakannyasag